Numerical analysis study of sarawak barrage river bed erosion and scouring by using Smooth Particle Hydrodynamic (SPH) - Zainol M.R.R.M.A.; Kamaruddin M.A.; Zawawi M.H.; Wahab K.A. (Institute of Physics Publishing, 2023)
Dams; Engineering research; Erosion; Fluid dynamics; River control; Rivers; Water levels; Laboratory experiments; Real case; River bed; Sarawak; Smooth particle hydrodynamics; Study areas; Three dimensional (3-D) modeling; Hydrodynamics